Description Of Depression Rates In Drug Case Inmates In Class II A Bulukumba Correctional Institution - Magfirah Ichlasul Amalia; Nurlina; Safruddin (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2021)
Depression is an affective disorder, which is generally characterized by loss of interest or excitement, reduced energy so that it is easily tired and reduced activity. Depression can occur in anyone and at any period. Depression disorders have increased from year to year this is supported by data, the World Health Organization WHO which states depression is a common disease that occurs in the world, there are about 264 million people who suffer from depression that increases from year to year about 76-85%. The goal is to identify the level of depression in drug inmates in The Correctional Institution Class II A Bulukumba Method used in this study is a descriptive design, which aims to get an overview of the level of depression in drug case inmates in The Correctional Institution Class II A Bulukumba. The affordable population in this study was inmates with drug cases, as many as 141 drug case inmates in the correctional institution Kls II A Bulukumba. The large sample in this study was 85 people. The researchers found results from 85 respondents (100%) obtained results for the highest depressed proposri is mild depression with the number of 55 (64.7%), while the lowest respondents who do not megalami depression with the number of 14 (16.5%). The conclusion of this study is that there is a picture of the level of depression of drug case inmates in the correctional institution class II A Bulukumba. And researchers suggest that the results of this study can be used as a material to increase insights in the field of research as well as increase knowledge about depression and drug cases at the Correctional Institution Class II A Bulukumba.